Penerapan mesin penyerut bambu pada pengrajin bambu irat sebagai upaya peningkatkan kualitas serutan bambu - Yuniwati, Ika; Fiveriaty, Anggra; Rahayu, Ninik Sri; Azizi, Muhammad Rizki; Affandi, Moh Nur (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Bamboo is a very easy plant found in Indonesia. This plant is very easy to grow and develops into many especially in tropical climates, so the bamboo is mostly grown on the river banks. Bamboo utilization is one form of an abundance of bamboo influences. Bamboo is widely used for the needs of making household and various kinds of crafts as well as wicker. This webbing is sold as a source for the makers’ income. Gintangan is a village located in Banyuwangi whose majority of people have the expertise of making wicker. Manufacture of webbing that requires thin bamboo sheets as raw material woven. Development of a bamboo ambush machine is needed to assist the partner in Gintangan Village as a tool to accelerate the process of making bamboo slices thin so that the manufacturing process becomes faster at the partner in Sanggar Kerajinan Bambu Karya Nyata. This bamboo-absorbing tool was developed to accelerate the process without having to do manual bamboo watering which is very time-consuming. The presence of these machines can increase the production of webbing rapidly and can increase the profit of partners because it reduces the cost for employees of the bamboo shredder.